Intelligence Measurement and School Performance in Latin America A Report of the Study of Latin American Intelligence Project - Flores-Mendoza, Carmen (Springer International Publishing, 2018)
This book presents the results of the most complete and updated assessment of cognitive resources of students in Latin America: the Study of Latin American Intelligence (SLATINT). During four years, top researchers of the region used a standardized set of cognitive measures to assess 4,000 students aged between 14 and 15 years from six countries: Brazil, Argentina, Mexico, Chile, Colombia and Peru. The data collected and now analyzed in this volume is a first step to understand the human cognitive capital of the region, a crucial resource for any country today. Intelligence research has shown that the cognitive skills of a population are strongly associated with the school performance of its students and the development of a nation. This makes Intelligence Measurement and School Performance in Latin America a valuable tool both for Latin American researchers and authorities engaged in the improvement of each country's human resources and for psychologists, educators and other social scientists dedicated to the study of the impact of intelligence in the development of nations. .